Prognostic significance of muc4 expression in gallbladder carcinoma - Lee Hyeon; Cho Min-Sun; Kim Tae (World Journal of Surgical Oncology, 2012)
Abstract Background Mucins are high molecular glycoproteins and play protective and lubricating roles in various epithelial tissues. Deregulated expression of mucins is involved in carcinogenesis and tumor invasion. MUC4 expression has been identified as a poor prognostic factor in pancreatobiliary carcinomas. To date, the relation between MUC4 expression and prognosis in gallbladder carcinoma remains to be determined. Authors examined MUC4 expression in gallbladder carcinoma and investigated its impact on prognosis. Methods The expression profiles of MUC4, MUC1, MUC2 mucins in gallbladder carcinoma tissues from 63 patients were investigated using immunohistochemical staining. Results For gallbladder carcinoma, positive staining of MUC4, MUC1, and MUC2 was 55.6%, 81.0%, 28.6%, respectively. There was a significant correlation between the expression of MUC4 and the expression of MUC1 or MUC2 (p = 0.004, p = 0.009, respectively). Univariate analysis showed that MUC4 expression (p = 0.047), differentiation (p < 0.05), T-stage (p < 0.05) and lymph node metastasis (p < 0.001) were significantly associated with poor survival. Expression of MUC1 and MUC2 was not correlated to survival. The backward stepwise multivariate analysis showed that MUC4 expression (p = 0.039) and lymph node metastasis (p = 0.001) were significant independent risk factors. In combined assessment of MUC4 and MUC2 expression, MUC4 positive and MUC2 negative group showed a significantly worse outcome than MUC4 negative groups(MUC4-/MUC2+ and MUC4-/MUC2-) and MUC4/MUC2 co-expression group(MUC4+/MUC2+) (p < 0.05). Conclusions MUC4 expression in gallbladder carcinoma is an independent poor prognostic factor. Therefore, MUC4 expression may be a useful marker to predict the outcome of patients with surgically resected gallbladder carcinoma. MUC2 expression may have prognostic value when combined with MUC4 expression.